Effectiveness Trial of an Intensive Communication Structure for Families of Long-Stay ICU Patients - Daly, Barbara J. (American College of Chest Physicians, 2010)
BACKGROUND: Formal family meetings have been recommended as a useful approach to assist in goal setting, facilitate decision making, and reduce use of ineffective resources in the ICU. We examined patient outcomes before and after implementation of an intensive communication system (ICS) to test the effect of regular, structured formal family meetings on patient outcomes among long-stay ICU patients. METHODS: One hundred thirty-five patients receiving usual care and communication were enrolled as the control group, followed by enrollment of intervention patients (n = 346), from five ICUs. The ICS included a family meeting within 5 days of ICU admission and weekly thereafter. Each meeting discussed medical update, values and preferences, and goals of care; treatment plan; and milestones for judging effectiveness of treatment. RESULTS: Using multivariate analysis, there were no significant differences between control and intervention patients in length of stay (LOS), the primary end point. Similarly, there were no significant differences in indicators of aggressiveness of care or treatment limitation decisions (ICU mortality, LOS, duration of ventilation, treatment limitation orders, or use of tracheostomy or percutaneous gastrostomy). Exploratory analysis suggested that in the medical ICUs, the intervention was associated with a lower prevalence of tracheostomy among patients who died or had do-not-attempt-resuscitation orders in place. CONCLUSIONS: The negative findings of the main analysis, in combination with preliminary evidence of differences among types of unit, suggest that further examination of the influence of patient, family, and unit characteristics on the effects of a system of regular family meetings may be warranted. Despite the lack of influence on patient outcomes, structured family meetings may be an effective approach to meeting information and support needs. TRIAL REGISTRY: ClinicalTrials.gov; No.: NCT01057238 ; URL: www.clinicaltrials.gov